The baton of death orchestrating life - Altair Macedo Lahud Loureiro; Carolina Silveira Muniz Ventura (Faculdade de Medicina de Botucatu (Unesp), 2008)
Making references to other analyzers of death, I present notes on death organizing life. I hold the idea that death is needed to give meaning to life in this human search of completeness. I look into a special situation of regarding death: the reaction of the individuals when witnessing and feeling the death of their aged ones; the reaction of someone, being a relative or not, who assumes their care and follows their imminent end; of individuals witnessing powerlessly, the hour of the lonely departure of their elder. Lonely and exclusive death, proper of that aged ones of whom we used to took care of, and their natural end, as a human being.